Health Status of Seagrass Beds in Intertidal Zone of West Sekotong West Lombok - Anisa Nurfitriani; Dining Aidil Candri; Sri Puji Astuti; Hilman Ahyadi; Suripto (Postgraduate, University of Mataram, 2026)
The coastal waters of West Sekotong possess significant potential in fisheries and marine resources. Seagrass is one of the key biotas contributing nutrients to support the fertility of surrounding waters. This study, conducted from May to July 2021 aimed to identify seagrass species and assess the health status of seagrass bed based on percentage cover and ecological indices. The research method used was purposive sampling with three research stations and systematic random sampling with transects. Based on the research that has been conducted, the following results were obtained seven seagrass species from two families. Hydrocharitaceae families (Enhalus acoroides, Thalassia hemprichii, Halophila ovalis, Halophila minor) and Cymodoceaceae families (Cymodocea rotundata, Cymodocea serrulata, Halodule pinifolia). The highest species density was H. pinifolia (119.47 ind/m²), with the highest important value index at station 1 (H. pinifolia 89%), station 2 (T. hemprichii 205%), and station 3 (E. acoroides 300%). Station 1 had the highest diversity and uninformity index, while station 3 was dominated by single species. Seagrass cover ranged from 31–48.33%, indicating unhealthy conditions, although environmental parameters remained within suitable ranges for seagrass growth.